2023
DOI: 10.1002/admi.202202105
|View full text |Cite
|
Sign up to set email alerts
|

Textile‐based Thermoelectric Generator Produced Via Electrochemical Polymerization

Abstract: The recent development in the field of wearable electronics has increased the demand for batteries as power sources which are subjected to periodic recharging and replacement. Therefore, the next challenge is to design new systems for sustainable energy to power portable electronic devices that can be easily integrated into textiles such as thermoelectric generators that can convert waste heat into electricity. Looking at this scenario, this work shows a methodology to prepare thermoelectric textiles by electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“… Qbadbreak=κnormalΔTnormalΔx$$\begin{equation}Q = - \kappa \frac{{\Delta T}}{{\Delta x}}\end{equation}$$where Q is the previously obtained heat flux value, Δ T is the temperature difference across the sample, and Δ x is the distance of heat transfer (the thickness of the sample). [ 33 ] All samples were tested at a pressure of 10 kPa.…”
Section: Methodsmentioning
confidence: 99%
“… Qbadbreak=κnormalΔTnormalΔx$$\begin{equation}Q = - \kappa \frac{{\Delta T}}{{\Delta x}}\end{equation}$$where Q is the previously obtained heat flux value, Δ T is the temperature difference across the sample, and Δ x is the distance of heat transfer (the thickness of the sample). [ 33 ] All samples were tested at a pressure of 10 kPa.…”
Section: Methodsmentioning
confidence: 99%
“…With the advancement of thermoelectric science and technology, the morphology of weavable thermoelectric materials has become diverse, and the research focus in this field continues to evolve. Generally, research focus areas in weavable thermoelectrics can be categorized as indicated by figure 2, including 1D fibers [42,43, and nanowires (NWs) [167,168], 2D thin films [169][170][171][172], 3D fabrics [173][174][175][176][177][178][179][180][181][182][183][184][185][186], device assembling [42,43,124], simulations [187,188], and integrations [189]. Among them, thermoelectric fibers with typical 1D macroscopic morphologies have garnered significant research attention.…”
Section: Classifications Of Weavable Thermoelectricsmentioning
confidence: 99%
“…Another research emphasis includes the design of substrates or supports that match woven thermoelectric fibers, such as common fabrics, flexible strings, and silicone. These support materials can serve solely as structural supports [173][174][175] or be thermoelectrically functionalized [176][177][178][179][180][181][182][183][184][185][186].…”
Section: Classifications Of Weavable Thermoelectricsmentioning
confidence: 99%
See 2 more Smart Citations